Learn Wireshark : Confidently Navigate the Wireshark Interface and Solve Real-World Networking Problems. - Bock, Lisa (Packt Publishing, Limited, 2019)
Learn Wireshark provides a solid overview of basic protocol analysis. The book shows you how to navigate the Wireshark interface, so you can confidently examine common protocols such as TCP, IP and ICMP. You'll learn tips on how to use display and capture filters, save, export, and share captures, and tips on how to troubleshoot latency issues.